Microlearning untuk Pengembangan Literasi Awal: Studi Kasus Kualitatif tentang Keterlibatan Anak dalam Pembelajaran Membaca Permulaan di Pendidikan Anak Usia Dini - Ode Sari Amalia, Wa; Maharani Puspita Wulandari, Waode; Salma, Sitti (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2026)
Early literacy development is a critical foundation for children's future academic success, yet conventional instructional approaches often fail to accommodate young children's limited attention span and learning characteristics. Although microlearning has been widely recognized as an effective instructional strategy, evidence regarding its implementation and contribution to beginning reading development in early childhood education remains limited. This study aimed to explore the implementation of microlearning and examine its contribution to learner engagement and beginning reading development in kindergarten. A qualitative case study was conducted at TK Al-Manshurin, Kendari, Indonesia. Data were collected through semi-structured interviews with the principal and a classroom teacher, participant observations involving 14 children, and document analysis. The data were analyzed using the Miles and Huberman interactive model, while credibility was ensured through triangulation and member checking. The findings indicate that microlearning was implemented through structured lesson planning, short learning sessions, and multimodal learning resources, including picture cards, short videos, songs, and educational games. These practices enhanced children's attention, participation, motivation, and confidence while progressively improving letter recognition, syllable decoding, word reading, and simple sentence reading. The study demonstrates that the effectiveness of microlearning extends beyond short instructional units, relying on well-designed pedagogy, teacher creativity, immediate feedback, and active learner participation. These findings position microlearning as an effective pedagogical strategy for strengthening early literacy development in early childhood education.